2003
DOI: 10.1100/tsw.2003.98
|View full text |Cite
|
Sign up to set email alerts
|

The Neurological Significance of Abnormal Natural Killer Cell Activity in Chronic Toxigenic Mold Exposures

Abstract: Toxigenic mold activities produce metabolites that are either broad-spectrum antibiotics or mycotoxins that are cytotoxic. Indoor environmental exposure to these toxigenic molds leads to adverse health conditions with the main outcome measure of frequent neuroimmunologic and behavioral consequences. One of the immune system disorders found in patients presenting with toxigenic mold exposure is an abnormal natural killer cell activity. This paper presents an overview of the neurological significance of abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
2
10
0
3
Order By: Relevance
“…On the basis of the obtained cytotoxicity assessment results of the extracts from the spores of 9 moulds, Schultz et al draws the conclusions on the potential risk for health as the result of the toxic influence after a significant inhalation of a large number of mould spores [21]. Similar observations may be found in the works of Anyanwu et al [5] and Pieckova [6], mentioned in the foreword for this article.…”
Section: Ijomeh 2017;30(2)supporting
confidence: 68%
See 2 more Smart Citations
“…On the basis of the obtained cytotoxicity assessment results of the extracts from the spores of 9 moulds, Schultz et al draws the conclusions on the potential risk for health as the result of the toxic influence after a significant inhalation of a large number of mould spores [21]. Similar observations may be found in the works of Anyanwu et al [5] and Pieckova [6], mentioned in the foreword for this article.…”
Section: Ijomeh 2017;30(2)supporting
confidence: 68%
“…Although species of Aspergillus non fumigatus, such as: A. flavus, A. ochraceus, A. niger, A. versicolor or A. terreus, are rarely aetiology factors of infections, they may be highly toxic [1][2][3][4]. It might be proven by other written sources that fungi belonging to Aspergillus fumigatus species are characterized by the highest toxicity among all the species belonging to this genus [5,6]. Aflatoxin B1, ochratoxin A as well as gliotoxin produced by the fungi belonging to A. fumigatus species are found to be responsible for such high toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women in our study attributed specific health problems they experience to their (women's) disproportionate consumption of damaged grains and exposure to toxic mold and chemicals associated with post‐harvest losses/activities. Notably, the women's health complaints fit with findings from epidemiological studies, which note similar presentations common to patients exposed to mycotoxins and these presentations include: liver problems, coughing, cancer in the respiratory system, chronic fatigue, headaches, and more (Anyanwu, Campbell, Jones, Ehiri, & Akpan ; Rheeder et al, ; Shephard, ). As such, our study supports several aforementioned studies that find mycotoxins play a negative role with regards to nutrition and health outcomes.…”
Section: Discussionsupporting
confidence: 54%
“…In stressed students, a short period (minutes) of preparation for a written exam induced the production of proinflammatory cytokines, which could be related to a Th1 response. Nevertheless, prolonged mental stress (of several days) caused deregulation of immune function, with a change in the cytokine response to a Th2 response.Anyanwu E et al 2003 [117]Abnormal NK cell activity was found in patients exposed to toxigenic materials, leading to adverse health conditions, including a wide range of neuroimmune and behavioral consequences.Ho C et al 2001 [118]Measurable changes in dendritic cell abundance were observed in patients undergoing surgery. These cells were rapidly mobilized in the circulation in response to surgical stress, and this activity may prepare host immune defenses against trauma.Woiciechowsky C et al 1998 [119]In patients with sympathetic activation due to acute accidental brain trauma, rapid systemic release of the anti-inflammatory cytokine IL10 from non-stimulated monocytes occurs.…”
Section: Pathophysiology Of the Psychoneuroendocrine Axismentioning
confidence: 99%